The Effect of Game-Based Learning in Physical Education to Improve Social Interaction and Physical Fitness of Students at State Junior High school 40 Bandung - Salsa Nabila Wardhani; Reshandi Nugraha; Riansyah (Journal of Physical Education Health and Sport, 2025)
This study aims to examine the effect of Game-Based Learning (GBL) in Physical Education (PE) learning on social interaction and physical fitness of junior high school students. The method used is a quasi-experimental design with a Non-randomized Control Group Pretest-Posttest Design. The research subjects consisted of 62 eighth-grade students of State Junior Higschool 40 Bandung who were divided into an experimental group and a control group. Social interaction was measured using the Social Provisions Scale (SPS) questionnaire, while physical fitness was measured through the Nusantara Student Fitness Test (TKPN) which includes the Pacer Test, V-Sit and Reach, Sit Up, and Squat Thrust. The results of the analysis showed that social interaction data were normally distributed and were analyzed using a Paired Sample t-Test, while physical fitness data were not normally distributed and were analyzed using the Wilcoxon Signed-Rank Test. The Mann-Whitney U Test was used to compare improvements between groups. The results showed a significant increase in social interaction and physical fitness in the experimental group, while the control group showed no significant changes. Effect size analysis showed a large effect on social interaction (r=0.56) and a moderate effect on physical fitness (r=0.46). These findings indicate that Game-Based Learning is effective in improving the quality of physical education (PE) learning in junior high schools.